(untitled) (Proceeding of Saizu International Conference on Transdisciplinary Religious Studies, 2023)
ملخص : من المهارات الأساسية في اللغة العربية هي مهارة القراءة من حيث أنها سبب لفهم النصوص من القرآن الكريم والحديث الشريف والعلوم المختلفة. وفي عصر الآن، أن هناك مجلة علمية مخصوصة مناسبة بعلومها. وفي جامعة والى سونجو الإسلامية الحكومية سمارانج إندونيسيا أن فيها نظام لاتصال المحاضرة بالبحوث العلمية المنتج بها المحاضرون ومنشور أو تم طرده في المجلة العلمية الخاصة. وأحد المواد الموجودة هي القراءة الصامتة. انطلاقا من تلك المتطلبة، فأراد الباحثان أن يبحثا في إشكالية مصطلح سردى عن البحوث في المجلات العلمية وتطبيق استخدامها في القراءة الصامتة لدى الطلاب الجامعية. طريقة البحث المستخدمة هي التصميم التجريبى pre-experimental design بنموذج دراسة حالة طلقة واحدة One – Shoot Case Study. المدخل المستخدم هو الوصفي النوعي التحليلي. والعينة لهذا البحث هي الطلاب جامعة والى سونجو الإسلامية الحكومية على مستوى الثانى بعدد 141 شخصا. طريقة أخذ العينة هي العمدية والعشوائية. طريقة جمع البيانات هي الملاحظة والمقابلة والتوثيق والتثليث المشترك. وتحليل البيانات بنموذج سبريدلي Spradley الذي يتكوّن على أربع نشاطات وهي التحليل المجالى والتحليلى الضريبى وتحليل المكوّنات وتحليل الموضوعى الثقافى. ونتيجة البحث أن إشكالية مصطلح سردى عن البحوث في المجلات العلمية في تطبيق تعليم القراءة الصامتة تتكوّن على إشكال الكلمات الجديدة وغرائب استماعها قبل وملاءمة النص بالسياق وتحليل محتوى النص. الكلمات الأساسية: مصطلح سردى؛ مجلة علمية؛ قراءة صامتة؛ طلاب جامعية؛ تعليم اللغة العربية Abstract: One of the basic skills in the Arabic language is the skill of reading in that it is a reason for understanding texts from the Holy Qur’an, Hadith and various sciences. Nowadays, there is a specialized scientific magazine that is suitable for its sciences. And at the Walisongo State Islamic University, Semarang, Indonesia, there is a system for connecting the lecture with the scientific research produced by the lecturers and published or expelled in the private scientific journal. One of the subjects that exists is silent reading. Based on this requirement, the two researchers wanted to investigate the problematic of the term narrative about research in scientific journals and the application of its use in silent reading among university students. The research method used is a pre-experimental design with a one-shot case study model. The approach used is descriptive, qualitative, analytical. The sample for this research is the students of Wali Songo State Islamic University at the second level, with a number of 141 people. The sampling method is intentional and random. The data collection method is observation, interview, documentation and joint triangulation. And data analysis using the Spradley model, which consists of four activities: field analysis, tax analysis, component analysis, and cultural objective analysis. Keywords: Narrative Term; Scientific Journal; Silent Reading; University Students; Teaching Arabic.